(untitled) (The São Paulo Journal of Mathematical Sciences, 2011)
In this note we describe how to approximate some classes of singular equations by nonsingular equations. We obtain a solution to each nonsingular problem and estimates guaranteeing that the limiting function is a solution of the original problem.